PENGARUH BUDGETARY GOAL CHARACTERISTICS DAN KOMPENSASI TERHADAP KINERJA APARAT PEMDA DENGAN KEPUASAN KERJA DAN MOTIVASI SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Dinas Di KabupatenKampar ) - Yurnita '; Hardi '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This purpose of this research is to analyze the effect of the characteristics of budget goals and compensation towards the performance of Kampar regency government officials, with job satisfaction and job motivation as an moderating variable. The research was based on sample of local government officials who have a direct relationship with the planning and execution of local budgets in the SKPD and Local Government Department in Kampar regency. The analytical method used in this research is the analysis model Moderating Regression Analysis (MRA) using SPSS. The results of this study show that: 1) Budgetary Goal Characteristics does not affect the performance of Civil Servants in Local Government Kampar. 2) Compensation affect the performance of Civil Servants in Local Government Kampar. 3) Job satisfaction is a moderator variable of variables Budgetary Goal Characteristics on the performance of civil servants in the Local Government Kampar regency. 4) Motivation is a moderator variable of Budgetary Goal Characteristics on the performance of civil servants in the Local Government Kampar regency. 5) Job satisfaction is a moderator variable of variable compensation to the performance of civil servants in the Local Government Kampar regency. 6) Motivation is a moderator variable of variable compensation to the performance of civil servants in the Local Government Kampar regency.Keyword : Public Budgetary,Compensation, Motivation, Performance, and Organization.